Attention-deficit/hyperactivity disorder–specific stimulant misuse, mood, anxiety, and stress in college-age women at high risk for or with eating disorders. Issue 4 (18th May 2016) - Gibbs, Elise L.; Kass, Andrea E.; Eichen, Dawn M.; Fitzsimmons-Craft, Ellen E.; Trockel, Mickey; Wilfley, Denise E.; , C. Barr Taylor
ABSTRACT: Objective : To examine the misuse of attention-deficit/hyperactivity disorder (ADHD)-specific stimulants in a college population at high risk for or with clinical or subclinical eating disorders.Participants : Four hundred forty-eight college-age women aged 18–25 at high risk for or with a clinical or subclinical eating disorder.Methods : Participants completed assessments of stimulant misuse and psychopathology from September 2009 to June 2010.Results : Greater eating disorder pathology, objective binge eating, purging, eating disorder–related clinical impairment, depressive symptoms, perceived stress, and trait anxiety were associated with an increased likelihood of stimulant misuse. Subjective binge eating, excessive exercise, and dietary restraint were not associated with stimulant misuse.Conclusions : ADHD-specific stimulant misuse is associated with eating disorder and comorbid pathology among individuals at high risk for or with clinical or subclinical eating disorders. Screening for stimulant misuse and eating disorder pathology may improve identification of college-age women who may be engaging in maladaptive behaviors and inform prevention efforts.